Український гранд-наратив. Ретроспективи та перспективи - Колесник, І. (Інститут історії України НАН України, 2008)
In this article grand-narrative (Metanarrative, Master Narrative, theoretical history) is presented as a key concept and ideology of Modernism. Classical European metanarrative created Image of Linear History that has been teleological, i deological, exclusive and Eurocentric. M.Hrushevsky’s scheme of Ukrainian history was the first model of the national metanarrative. In the late 20th century J.-F. Lyotard fixed crisis of classical grand-narrative and advocated relativism as antidote to grand - narrative. Today’s historiography is characterized by process of the metanarrative rebirth. After analyzing the relevant literatures author proposes the new model of national grand -narrative – structural and synergetic conception of Ukrainian History.